Perancangan Implementasi ISO 9001:2015 di PT. Wellgan Gemilang - Elma Cathlin Tangradi; Jani Rahardjo (Jurnal Titra, 2018)
Designing the document and system is an initial step to fulfill the requirement of ISO 9001: 2015. The fulfillment of the requirements of ISO 9001: 2015 starts with conducting a gap analysis between documents or systems required by ISO 9001: 2015 with existing documents or systems at PT Wellgan Gemilang. These preliminary findings resulted an initial gap of 26.06%. The fulfillment of the requirements of ISO 9001: 2015 is done by designing documents and system, begins with conducting strengths and weaknesses (SWOT) analysis of the company, business processes mapping, setting the vision, mission and quality policy, determining quality objectives, organizational structure and job analysis (Job Description) as well as competency matrix, Standard Operating Procedure (SOP) and Work Instruction (WI) for each process in business process and risk analysis for each department and quality objective. Design of document and quality management system ISO 9001: 2015 that has been done reflects the fulfillment of requirement increase from 26.06% to 61.97%.